EVALUATION REPORT OF CONSTRUCTION (state code – 653H20002) - Markou, George; Aavik, Andrus; Gaile, Liga; Stragys, Vincentas Vytis; Šimanauskas, Tautvydas (My University, 2016)
The evaluation of on-going study programmes is based on the Methodology for Evaluation of Higher Education Study Programmes, approved by the Order No 1-01-162 of 20th December 2010 of the Director of the Centre for Quality Assessment in Higher Education (hereafter, SKVC). Evaluation is intended to help higher education institutions to constantly improve their study programmes and to inform the public about the quality of studies.